2014
DOI: 10.1186/1471-2261-14-153
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between obesity, glycemic control, and cardiovascular risk factors: a pooled analysis of cross-sectional data from Spanish patients with type 2 diabetes in the preinsulin stage

Abstract: BackgroundObesity is associated with the onset of type 2 diabetes mellitus (T2D), but reports conflict regarding the association between obesity and macrovascular complications. In this study, we investigated associations between cardiovascular risk factors and body mass index (BMI) and glycemic control in non–insulin-treated patients with T2D.MethodsAuthors gathered cross-sectional data from five observational studies performed in Spain. Generalized logit models were used to analyze the relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 47 publications
(56 reference statements)
8
23
0
3
Order By: Relevance
“…BMI was inversely related to age in this study. This relationship between BMI and age is consistent with previous studies, which also demonstrated an inverse association with duration of diabetes [6,21]. Japanese patients with diabetes have quite limited insulin secretory capacity and are becoming obese during the early stages of the disease [22].…”
Section: Discussionsupporting
confidence: 81%
“…BMI was inversely related to age in this study. This relationship between BMI and age is consistent with previous studies, which also demonstrated an inverse association with duration of diabetes [6,21]. Japanese patients with diabetes have quite limited insulin secretory capacity and are becoming obese during the early stages of the disease [22].…”
Section: Discussionsupporting
confidence: 81%
“…It has also been suggested that an adverse metabolic profile in patients with normal weight increases the risk of subsequent development of T2DM and other CVD 65,66,68 . A recent study explored the relationship between obesity, glycaemic control and cardiovascular risk factors in T2DM patients who were not receiving insulin treatment and concluded that cardiovascular risk factors become more important as patients became more obese 65 .…”
Section: 13: Bmi Glycaemic Control and Obesity Paradox In T2dmmentioning
confidence: 99%
“…It has also been suggested that an adverse metabolic profile in patients with normal weight increases the risk of subsequent development of T2DM and other CVD 65,66,68 . A recent study explored the relationship between obesity, glycaemic control and cardiovascular risk factors in T2DM patients who were not receiving insulin treatment and concluded that cardiovascular risk factors become more important as patients became more obese 65 . This study also reported that younger age and more recent onset of the disease were associated with higher BMIs, suggesting that the development of an obese condition at an early age could be a significant factor underlying the increase in T2DM incidence 65 .…”
Section: 13: Bmi Glycaemic Control and Obesity Paradox In T2dmmentioning
confidence: 99%
See 2 more Smart Citations